Dynamic computable general equilibrium simulations in support of quantitative foresight modeling to inform the CGIAR research portfolio: Linking the IMPACT and GLOBE models - Willenbockel, Dirk; Robinson, Sherman; Mason-D'Croz, Daniel; Rosegrant, Mark W.; Sulser, Timothy B.; Dunston, Shahnila; Cenacchi, Nicola (International Food Policy Research Institute, 2018)
In the context of the project Quantitative Foresight Modeling to Inform the CGIAR Research Portfolio, IFPRI’s International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) was linked to the global dynamic computable general equilibrium model, GLOBE-Energy. This linkage is documented here to provide a detailed account of the methodological approach. GLOBE’s role within the analytical framework of the project is to assess the macroeconomic income and welfare effects associated with the alternative pathways for agricultural productivity under the different scenarios and to feed the simulated aggregate income time paths back to IMPACT.